Pengaruh Citra Merek dengan Ekuitas Merek Terhadap Keputusan Pembelian Teh Botol Sosro di Kota Semarang - Burhanudin Fakhri Kusuma; Djoko Setyabudi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
This research is based on the decline in sales and the Top Brand Index of Botol Sosro Tea in Semarang City, this condition is not in line with the increase in tea production and consumption in Indonesia which is continuously increasing. This study aims to find out about Brand Image with Brand Equity on Purchasing Decisions using the Nicosia model and to study brand image influencing purchasing decisions with the theory of reasoned action located in Semarang City. This study uses a survey with explanatory types with a sample of 80 people and taken by non probability sampling techniques. Data analysis using simple regression analysis. The image of the Teh Botol Sosro brand is categorized into four groups, namely: very bad, bad, good and very good at looking at the image of the Teh Botol Sosro brand. Having a discovery about the brand image of Teh Botol Sosro has a very good image. The Teh Botol Sosro brand equity formed from four dimensions namely, brand awareness, brand association, perceived quality, and brand loyalty are categorized into four categories, namely: very low, low, high, very high in relation to the mastery of the Teh Botol Sosro trademark. The result is that the ownership of the Teh Botol Sosro brand is very high. The decision to purchase Teh Botol Sosro is categorized into four categories from the results of the scores obtained from respondents, namely: very low, low, high, and very high in purchasing purchases of Teh Botol Sosro. Asking for the results of the decision to buy Teh Botol Sosro comes in the high category. The results of the study show. What is significant between brand image and brand equity. Successfully improving the image of the Teh Botol Sosro brand will increase the brand equity of Teh Botol Sosro. In the second hypothesis shows a significant effect between brand equity on purchasing decisions. Every successful purchase of the Teh Botol Sosro brand equity will increase the purchasing decision. The hypothesis of the two shows is significant between brand image and purchasing decision. Successfully every shot of the Teh Botol Sosro brand will increase purchasing decisions. So it is fitting for Teh Botol Sosro marketers to focus on increasing brand equity first through brand image and then influencing purchasing decisions. In further research, it is expected to examine other factors that can influence the purchasing decision of Teh Botol Sosro.